14C Variations in Pre-Bomb Nearshore Habitats of the Florida Panhandle, USA. Issue 3 (2015) - Hadden, Carla S; Cherkinsky, Alexander
Abstract : This article presents radiocarbon data for known-age, pre-bomb marine gastropods, Busycon sinistrum and Strombus alatus, collected between AD 1924 and 1946 from nearshore environments of the Florida Panhandle, on the northern Gulf of Mexico. Δ 14 C was measured in whole crushed juvenile specimens ( n = 7) and terminal edges of adult specimens ( n = 6). A subsample of adult specimens ( n = 3) was subjected to additional, intrashell sampling to observe short-term variability in 14 C conditions. Δ 14 C values were consistent within and among B. sinistrum specimens, and we propose a reservoir age offset (ΔR) of −9 ± 25 14 C yr for B. sinistrum from the northwest coast of Florida. S. alatus shells exhibited significant variability from one individual to another, and also within individual specimens. ΔR values for S. alatus range from −3 ± 30 to 659 ± 30 14 C yr. These differences may result from a combination of factors, including subregional variability in inputs of 14 C-depleted waters and life-history factors including mobility, mode of feeding, and ontogenetic niche shifts.